Рыбы-лимпофилы бассейна Верхнего Днестра. Сообщение II - Опалатенко, Л.К. (Вестник зоологии, 1970)
Scardinius erythrophtatmus (L.) and Tinea tinea (L.) are the typical limnophilous fishes of the upper Dniester basin. Their distribution is connected with stagnant or slowly flowing waters in the basins where their fattening and spawning take place. These fishes from the upper Dniester basin differ from those, described by L. S. Berg (1949) in the formula of unpaired fins and lateral line. The sexual dimorphism was observed in plastic characters. A list of plastic characters consists of 27—28 titles. Both species are of local industrial value.